The Influence of Parents Socio-Economic Status to Learning Achievement Through Learning Motivation of High School Students In Kuantan Tengah Subdistrict - Endang Prabandari; Syakdanur Nas; Gusnardi Gusnardi (Universitas Riau, 2020)
The aim of this study was to analyze the influence of parents’ socio-economic status on learning achievement through learning motivation of high school student at Subdistrict Kuantan Tengah. The population in this study was all high school students majoring in Social Science with the total of 426 students. Meanwhile, the total sample of this study was 206 students. The data were collected by using questionnaires. After that, the data were analyzed by using quantitative descriptive and path analysis. The results showed that the variables of parents’ socio-economic status had a significant influcence on learning achievement (directly), and it had a significant influence learning achievement through learning motivation (not directly) of high school students at Subdistrict Kuantan Tengah.